Cidadãos do império, alerta! a guarda nacional na Paraíba oitocentista (1831-1850) - Costa, Lidiana Justo da (2013)
This study is linked to the online research Regional History, the Graduate Program in History Federal University of Paraíba, with a major in History and Historical Culture, and aims to examine the creation and operation of the National Guard in the province of Paraiba (1831-1850). The creation of the National Guard, on August 18, 1831, was one among the various measures undertaken by the government regent, to ensure the unity of the national Brazilian state. This institution should be composed of those who were considered citizens of the Empire of Brazil, so they were prescribed in the Constitution of 1824. Therefore, besides investigating the creation of this institution in the province of Paraiba, we present the procedures involving its organization and functioning, as well as legal profiles / Ethnic some characters that composed their ranks. We will also provide a brief discussion of citizenship in the nineteenth century, shedding light on how this citizenship was experienced by militiamen in the province because, to them, fell the privilege of being part of the militia. We will review the daily actions of the missionaries of the order and attempts to find some guards to escape the ordinary service of the Guard - which, contrary to what had just tried the Act creating the National Guard from 1831: the "patriotism" of his militia. And when it comes to positions of command in the militia, will discuss the importance of this position gave the chosen, and over the years has become highly political.